Persepsi pekerja terhadap faktor perkembangan kerjaya :satu kajian di Komag USA di Samajaya, Kuching - Hussin, Abdul Al Rashid (University Malaysia Sarawak, UNIMAS., 2004)
This research was carried out to identify the perception of employees on the factors of career development. Research was carried out on one organization only, which is KOMAG USA (M) Sdn bhd (Sarawak Operational). Beside that, this research was also carried out to determine the existent of perception level base on demography's factor. Practical, suitable career and promotion were among factor (Jf career development, which have been chosen. Demography characteristic, which have been chosen, were income, education and age. Demography characteristic was considered to strengthen the ofemployee's perception on career development factor. 50 respondents involved in this research and all ofthem were general staff. Results shows that many of. them have positive perception on factor of career development. Result also shows that there is significant relationship between perception of employees and factors of career development base on practical, suitable career and promotion. Among the demography's factor chosen, only age shows different in perception of employees. Through this research, author would like to suggest that factors which have been studied should be observe and further action should be taken by the employers. Beside that, author can concentrate on one organization only involving employees and employers as respondents in future.